1986
DOI: 10.1203/00006450-198606000-00001
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Subclass Distribution And Human Cord Blood Lipid Levels

Abstract: ABSTRACT. The high-density lipoprotein (HDL) subclass distribution was examined by gradient gel electrophoresis (gge) in 154 human cord blood samples, and determinations of triglyceride, total cholesterol, and HDL-cholesterol levels were performed. Three distinct gge patterns were recognizable. The first pattern, termed the normal (gge) pattern, was distinguished by a prominent double peak in the (HDL2,),, region and a pronounced peak in the (HDL3b)gge region. Minor peaks, or shoulders, were also seen in the (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This is not unexpected since increased plasma cholesterol in premature infants has been previously reported (7)(8)(9). Cord blood TG levels of the infants in this study are comparable to those reported for normal term infants (2). After enteral feedings, both the mean TG and TC are significantly elevated at both sampling times compared with cord blood (Table 2).…”
Section: Population Samples Premature Infants Born At a High Risksupporting
confidence: 73%
See 4 more Smart Citations
“…This is not unexpected since increased plasma cholesterol in premature infants has been previously reported (7)(8)(9). Cord blood TG levels of the infants in this study are comparable to those reported for normal term infants (2). After enteral feedings, both the mean TG and TC are significantly elevated at both sampling times compared with cord blood (Table 2).…”
Section: Population Samples Premature Infants Born At a High Risksupporting
confidence: 73%
“…Unlike adult HDL, normal cord blood has a paucity of particles in the (HDL3,),, region, and two distinct components within the (HDL,,),, region. This normal cord blood HDL subclass distribution correlates with plasma cholesterol levels < 85 mg/dl and TG levels < 65 mg/dl (2). In addition to the normal (gge) pattern, two other (gge) patterns have been identified in newborn infants and, in both instances, were associated with abnormal plasma lipid levels (2).…”
Section: Tg Triglyceride Vldl Very Low-density Lipoproteinsmentioning
confidence: 99%
See 3 more Smart Citations